Electroencephalographic study of auditory system while listening to Ohm chanting - Sachdev, Sasithorn; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: World Health Organization defined that we must have Physical, Mental, Social and Spiritual Well-Being. The methods of building a healthy body and develop a strong immune are food, exercising, walking, running, yoga, swimming, Tai Shi Shuan and all types of sports. In spiritual well-being, the implementations are practice the dharma, compassionate prayer and meditation. These will make our mental status always in good state, greed, anger and infatuation will be decreased. Aims and Objective: This study aimed to investigate the effect of listening to Om chanting on human brain waves. Materials and Methods: The samples were twelve healthy Thai citizens with the age ranged between twenty-five and sixty years old. All participants listened to Ohm chanting for thirty minutes, with rest time in between. During the experiment, the participants were asked to open their eyes. In addition, their brain wave activities were recorded before, during and after listening to the Ohm chanting by the Electroencephalogram (EEG) at precise intervals. All data were tabulated to find mean and standard deviation. The changes in brain waves and subjective changes were also compared by applying paired t-test. People listening to Ohm chanting had subjective changes through electroencephalographic (EEG) fluctuations. Results: The exposed participants displayed statistically significant increases in delta and theta brainwaves at 0.05 after listening to Ohm chanting. This study revealed that participants were trained with the listening to Ohm chanting causing probably the stress level went down. There was an increase in delta and theta brainwaves while listening to Ohm chanting. Conclusion: The result might be nominated for health promotion to be used in conjunction with conventional medicine.